Research on solidified shell thickness in continuous casting blank. Issue 1 (1st December 2022) - Li, Huicheng; Wang, Haixin; Yu, Fei; Liu, Haining; Chen, Tingjun; Liu, Sheng
Abstract: The stability of solidified shell thickness plays an important role in continuous casting. In this paper, 220mm × 260mm section continuous casting blank of an electric furnace company is taken as the research object. Under the condition of solidification process, the solidification shell thickness is simulated by the physical model established and ANSYS software. At the same time, according to the calculation formula of solidified shell thickness, combined with the specific data location of the designed and measured solidified shell thickness test, the good match between the experimental calculation and the model prediction is achieved. It provides a reliable basis for following F-EMS optimization and essential data sustain for the transformation and promotion of solidified structure of the blank under light pressure soft reduction.